L-Carnitine Alleviates the Myocardial Infarction and Left Ventricular Remodeling through Bax/Bcl-2 Signal Pathway. (23rd May 2022) - Li, Hao-Ran; Zheng, Xiao-Ming; Liu, Yan; Tian, Jing-Hui; Kou, Jie-Jian; Shi, Jun-Zhuo; Pang, Xiao-Bin; Xie, Xin-Mei; Yan, Yu
Abstract : Purpose . L-carnitine (LC) is considered to have good therapeutic potential for myocardial infarction (MI), but its mechanism has not been clarified. The aim of the study is to elucidate the cardioprotective effects of LC in mice following MI and related mechanisms. Methods . ICR mice were treated with LC for 2 weeks after induction of MI with ligation of left anterior descending artery. Electrocardiographic (ECG) recording and echocardiography were used to evaluate cardiac function. H&E staining, TTC staining, and Masson staining were performed for morphological analysis and cardiac fibrosis. ELISA and immunofluorescence were utilized to detect biomarkers and inflammatory mediators. The key proteins in the Bax/Bcl-2 signaling pathway were also examined by Western blot. Results . Both echocardiography and histological measurement showed an improvement in cardiac function and morphology. Biomarkers such as LDH, NT-proBNP, cTnT, and AST, as well as the inflammatory cytokines IL-1 β, IL-6, and TNF- α, were decreased in plasma of mice receiving LC treatment after myocardial injury. In addition, the expression of α -SMA as well as the key proteins in the Bax/Bcl-2 signaling pathway in cardiac myocardium were much lower in mice with LC treatment compared to those without after MI. Conclusions . Our data suggest that LC can effectively ameliorate left ventricular (LV) remodeling after MI, and its beneficial effects on myocardial function and remodeling may be attributable at least in part to anti-inflammatory and inhibition of the Bax/Bcl-2 apoptotic signaling pathway.